REPRESENTASI DIRI PEREMPUAN, PEMBUNGKAMAN KAPASITAS DIRI PEREMPUAN, DAN LITERASI MEDIA SEBAGAI SEDIKIT FENOMENA MASALAH GENDER DAN SOLUSINYA - Ino Sulistiani (AN-NISA, 2024)
Gender issues are complex issues involving fundamental aspects of human life. When we discuss gender issues, we highlight the inequalities, discrimination and stereotypes that still exist in many societies. Women often face limitations that hinder their full potential in areas such as work, education and social life. In the context of spirituality, society often has religious norms and interpretations that can lead to discrimination against individuals based on sex, sexual orientation, or gender identity. A rigid understanding of spirituality can curb individuals' freedom to live their lives in accordance with personal values and human rights. Silencing women is a way of intimidating women's rights to develop both financially and economically. By eliminating intimidation against women, women can represent themselves according to their own image, either as empowered women or building feminism using social media. Online media can be used as a creative effort to carry out gender sensitive journalism and advocacy journalism as a means of media literacy that can educate women to become intelligent women who do not directly accept the information provided but must be able to properly analyze the values contained in the information they obtain. Keywords:  Women, Gender, Women's Self-Representation, Silencing of                   Women's Self-Capacity, Media Literacy